Defects in Vascular Mechanics Due to Aging in Rats: Studies on Arterial Wave Properties from a Single Aortic Pressure Pulse - Chang, Chun-Yi; Chang, Ru-Wen; Hsu, Shu-Hsien; Wu, Ming-Shiou; Cheng, Ya-Jung; Kao, Hsien-Li; Lai, Liang-Chuan; Wang, Chih-Hsien; Chang, Kuo-Chu (Frontiers in Physiology, 2017)
Changes in vascular mechanics due to aging include elevated vascular impedance, diminished aorta distensibility, and an accelerated return of pulse wave reflection, which may increase the systolic workload on the heart. Classically, the accurate measurement of vascular mechanics requires the simultaneous recording of aortic pressure and flow signals. In practice, it is feasible to estimate arterial wave properties in terms of wave transit time (τw) and wave reflection index (RI) by using aortic pressure signal alone. In this study, we determined the τw and magnitudes of the forward (∣Pf∣) and backward (∣Pb∣) pressure waves in Long–Evans male rats aged 4 (n = 14), 6 (n = 17), 12 (n = 17), and 18 (n = 24) months, based on the measured aortic pressure and an assumed triangular flow (Qtri). The pulsatile pressure wave was the only signal recorded in the ascending aorta by using a high-fidelity pressure sensor. The base of the unknown Qtri was constructed using a duration, which equals to the ejection time. The timing at the peak of the triangle was derived using the fourth-order derivative of the aortic pressure waveform. In the 18-month-old rats, the ratio of τw to left ventricular ejection time (LVET) decreased, indicating a decline in the distensibility of the aorta. The increased ∣Pb∣ associated with unaltered ∣Pf∣ enhanced the RI in the older rats. The augmentation index (AI) also increased significantly with age. A significant negative correlation between the AI and τw/LVET was observed: AI = −0.7424 − 0.9026 × (τw/LVET) (r = 0.4901; P < 0.0001). By contrast, RI was positively linearly correlated with the AI as follows: AI = −0.4844 + 2.3634 × RI (r = 0.8423; P < 0.0001). Both the decreased τw/LVET and increased RI suggested that the aging process may increase the AI, thereby increasing the systolic hydraulic load on the heart. The novelty of the study is that Qtri is constructed using the measured aortic pressure wave to approximate its corresponding flow signal, and that calibration of Qtri is not essential in the analysis.